IDENTIFIKASI JAHE – JAHEAN (ZINGIBERACEAE) DI KAWASAN HUTAN LINDUNG GUNUNG BAWANG KABUPATEN BENGKAYANG KALIMANTAN BARAT - Sepito, Bendril; Manurung, Togar Fernando; Kartikawati, Siti Masitoh (Universitas Tanjungpura, 2019)
Family Zingiberaceae is one of flowing plant known by the community as ginger. Many Zingiberaceae found in tropical forest areas, especially Indo-Malaya. There are around 50 % genus growth in lowland forest more than 2000 masl. The purpose of this study was to identify the ginger species (Zingirberaceae) of protected forest in Gunung Bawang Bengkayang Regency West Kalimantan. The method used in this research was survey purposive determination starting point. The survey consisted of 5 transect that length at 200 m. The results showed that gingers species found in Gunung Bawang was 17 gingers species, that were classified into 6 Genus. Globba propingua Ridl was found with the highest number of species. Overall, the research showed that the Gunung Bawang is in a good state and to be maintained.Keyword: Gunung Bawang, Gingers, Protected forest, Zingiberaceae